The inflammatory environment mediated by a high-fat diet inhibited the development of mammary glands and destroyed the tight junction in pregnant mice. Issue 9 (3rd September 2020) - Guo, Wenjin; Liu, Juxiong; Hou, Shuang; Hu, Guiqiu; Ma, He; Gong, Qian; Kan, Xingchi; Ran, Xin; Cao, Yu; Wang, Jianfa; Fu, Shoupeng
Abstract : Long-term intake of a high-fat diet seriously affects the health of pregnant women and leads to increased levels of inflammation in the mammary gland. Abstract : Long-term intake of a high-fat diet seriously affects the health of pregnant women and leads to increased levels of inflammation in the mammary gland. Therefore, to further explore the effect of a high-fat diet on mammary gland development and the tight junction (TJ) during pregnancy, we placed mice into two groups: a high-fat diet group and a control group. We detected the expression of proteins related to fat synthesis in the mammary gland by western blotting. The results showed that a high-fat diet could lead to an increase in fat synthesis in the mammary gland. Then, the inflammatory levels and acinar cell morphology in the mammary gland were detected by ELISA and H&E staining. We also measured the levels of MAPK and NF-κB signal pathway-related proteins by western blotting. The results showed that a high-fat diet activated the MAPK and NF-κB signaling pathways and promoted the expression of inflammatory factors. Finally, the development of the mammary gland and the integrity of the TJ were determined by immunohistochemistry, immunofluorescence and western blotting. The results showed that a high-fat diet inhibited the development of the mammary gland and the expression of tight junction proteins (TJs). Our study showed that a high-fat diet could promote the expression of inflammatory factors by activating the MAPK and NF-κB signaling pathways and could reshape the microenvironment through extramammary inflammation. Finally, a high-fat diet inhibited the development of the mammary gland during pregnancy and destroyed the integrity of the TJ.